Screening for noncommunicable disease risk factors at a workplace in India: A physiotherapy initiative in a healthcare setting - Aditi Ravindra Ketkar, MPT; Sundar Kumar Veluswamy, MPTh, PhD; Nivedita Prabhu, MPT; Arun Gundmi Maiya, PhD (World Scientific Publishing, 2015)
Background: Noncommunicable diseases (NCDs) account for two-thirds of all deaths globally. Physiotherapists have the requisite expertise to initiate and lead NCD risk factor screening and prevention programmes. The workplace can provide an ideal setting for physiotherapists to screen for risk factors and implement prevention programmes. Objective: This study was designed to identify the common modifiable risk factors for NCD among employees of a healthcare institution. Methods: A cross-sectional study of NCD risk factors was conducted in a large healthcare teaching institution. Employees from four of the seven constituent institutes of the healthcare institution were evaluated using the World Health Organisation STEPS Instrument (Steps I and II). Continuous variables were expressed as mean ± standard deviation. Categorical variables and the prevalence of risk factors were expressed as frequencies and percentages. Results: A total of 247 employees (response rate 68.2%) participated in the study. Poor dietary habits, suboptimal blood pressure, and physical inactivity were identified as the most common modifiable NCD risk factors in this population. Conclusion: Knowledge of NCD risk factors can be used by physiotherapists to implement health promotion programmes in the workplace as a means of reducing NCD-related economic and social burdens in India.